Effects of aging on nitrergic neurons in human striatum and subthalamic nucleus - Bruno Lopes dos Santos-Lobato; Elaine Aparecida Del-Bel; José Eymard Homem Pittella; Vitor Tumas (Arquivos de Neuro-Psiquiatria)
Nitric oxide (NO) is a major neurotransmitter associated with motor control in basal ganglia. Movement disorders, as essential tremor and Parkinson’s disease, are more prevalent on aged individuals. We investigated the effects of aging on neuronal density and diameter/area of nitrergic neurons in samples of striatum (caudate and putamen) and subthalamic nucleus of 20 human brains from normal subjects, stained by histochemistry for NADPH-diaphorase and immunohistochemistry for neuronal NO synthase. Our data showed aging does not modify the neuronal density and size of nitrergic neurons in striatum and subthalamic nucleus. These findings suggest a lack of association between aging and morphologic changes on nitrergic neurons.